The Superiority of Mie Gacoan in Terms of Price Perception and Product Quality - Nanang Adie Setyawan (Cita konsultindo, 2023)
The global era, life can be associated with new things. The business conditions very competitive between companies and other SME`s where the level of competition eventually becomes very high. Regarding the price, customers will of course look for the lowest possible price but demand good quality from a product. Customer satisfaction is an important concern at this time because it will form customer loyalty. Research related to Price Perception, Product Quality, Consumer Satisfaction, and Customer Loyalty conducted on customers of gacoan noodle outlets in the city of Semarang consisting of students and workers in the age range of 15 to 40 years. This study uses confirmatory factor analysis and maximum likelihood estimation in SEM from the AMOS 24.0. The data collection technique uses a questionnaire with incidental sampling. The parameter estimation results are following the hypothesis that Price Perception and Product Quality significantly affect Consumer Satisfaction and have an impact on Customer Loyalty. From this research, it concluded that after the current Covid-19 pandemic, consumers are increasingly enthusiastic about dining with friends and family outside the home or ordering online by looking for dishes that fit their budget and looking for good product quality.